2006
DOI: 10.1159/000092853
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Baicalin on the Expression of Receptor Activator of Nuclear Factor-κB Ligand in Cultured Human Periodontal Ligament Cells

Abstract: Background: Baicalin is a flavonoid purified from the medicinal plant Scutellaria baicalensis Georgi. It has been reported that baicalin exhibits antibacterial, anti-inflammatory and analgesic effects and can inhibit nuclear factor-ĸB activation. Periodontal disease is a chronic infective disease of the periodontium caused by bacteria present in dental plaque inducing alveolar bone resorption until teeth are lost. Human periodontal ligament (HPDL) is the connective tissue between alveolar bone and tooth. Recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…It is important to note that PDL fibroblasts influence osteoclastogenesis. Wang et al 31 found that baicalin could inhibit the RANKL mRNA expression induced by interleukin‐1β in cultured HPLCs. The present results are consistent with that notion.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that PDL fibroblasts influence osteoclastogenesis. Wang et al 31 found that baicalin could inhibit the RANKL mRNA expression induced by interleukin‐1β in cultured HPLCs. The present results are consistent with that notion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, baicalin inhibited the pro-inflammatory gene expression via down-regulating the TLRs/NF-κB signaling, such as COX-2, iNOS, TNF-α , IL-6, IL-13 and HMBG-1 in cervical tissue and colon tissue [11,30,32]. In addition, baicalin inhibited the production of IL-1β, IL-8, PGE2, leukotriene B4 (LTB4), COX-2, RANKL/OPG ratio, and inhibited the NF-κB, p38 MAPK in many types of cells involved in the process of periodontitis, such as human gingival fibroblasts, periodontal ligament cells, oral keratinocytes and cultured osteoblasts [19,20,[34][35][36]. In our study, baicalin down-regulated of HMGB1, TNF-α, IL-1β, and MPO in gingival tissues by down-regulating the TLR2 and TLR4/MyD88/ NF-κB signaling, and reduced inflammatory infiltrates and MPO production possibly by affecting these types of inflammatory cells during the process of periodontitis.…”
Section: The Pharmacological Effects Of Baicalinmentioning
confidence: 99%
“…Functional ingredients derived from TCM have been shown to be powerful tools for the activation of adult stem cells for tissue regeneration, leading to the use of some of these molecules as useful adjuvants in cell processing technology and periodontal tissue engineering applications, sometimes as a substitute for recombinant human growth factors [39,40]. Particularly, osthole is a fundamental ingredient of coumarin compounds that are the main pharmaco-components of Fructus cnidii [41].…”
Section: Introductionmentioning
confidence: 99%